RTJ cu4tro [compact disc] - El-P (Rapper); Hook, Nick; Uzoigwe, Amaechi; Santa Fe Klan; Baco Exu Do Blues; Sarah La Morena; Individuo; Akapellah; Apache, 1964-2010; Pawmps; Williams, Pharrell; De La Rocha, Zack; et al. (Jewel Runners, 2022)
Run the Jewels have reimagined their hit album, RTJ4, through the prism of Latin America. This features appearances and remixes from Bomba Estereo, Danny Brasco, Iggor Cavalera, and a special appearance from Lin-Manuel Miranda.